THE INFLUENCE OF HUMORAL IMMUNITY ANTIENDOTOXIN RESPONSE TO INDICATORS OF SYSTEMIC INFLAMMATION IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - D. V. Shaduro (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
Introduction. Systemic lupus erythematosus (SLE) — severe autoimmune disease that has a high level of morbidity and mortality. With each decade the SLE incidence rate grows up. Current researches do not allow to identify the etiology of this disease. The polyclonal stimulation of T and B lymphocytes processes are prevailed in pathogenetic picture of the disease. One of the most powerful triggers of stimulation may be a gram-negative bacteria lipopolysaccharide (LPS) or endotoxin (ET). The impact activity is regulated by a specific humoral and cellular antiendotoxin immune response.Materials and methods. The study group involved 48 patients with SLE, the control group consisted of 40 healthy donors. The material of the study was the venous blood. The following indicators have been identified: the levels of specific anti-endotoxin antibodies (antiLPS IgA, IgM and IgG), by enzyme linked immunosorbent assay (ELISA); concentration of total immunoglobulins IgA, IgM and IgG — microturbidimethric method; the concentration of C-reactive protein (CRP) — ELISA; endogenous intoxication (EI) — a method of determining the average molecular weight for the absorption in the ultraviolet spectrum; circulating immune complexes (CIC) — the method of precipitation in polyethylene glycol. Statistical processing was performed using Microsoft Office Excel 2007 software and MedStat®.Results. The study showed a statistically significant increase in anti-LPSIgG SLE patients by 2.5 times compared with the control group. A slight increase in total IgG by 5%. Endogenous intoxication index in SLE patients was higher by 13.9%, CIC by 150%. The level of CRP in the study group was 6.8 times higher compared with the control. There were also identified the inverse correlation between anti-LPS-IgG and CRP, the inverse correlation between anti-LPS-IgG and EI, direct correlation between anti-LPS-IgA and the age of patients.Discussion. These results indicate the presence of dysfunction in the antiendotoxin immune response (AEIR) in SLE patients, namely increasing concentrations of specific anti-LPS-Ig. Identified growth of indicators of systemic inflammation correlated with indicators of AEIR, that confirms their mutual influence, which contributes to the lesion of organ-targets and can aggravate the manifestation and course of SLE. Normalization of AEIR, elimination of LPS may be a new way of treatment for SLE patients